A Tissue-Specific Landscape of Alternative Polyadenylation, lncRNAs, TFs, and Gene Co-expression Networks in Liriodendron chinense - Tu, Zhonghua; Shen, Yufang; Wen, Shaoying; Liu, Huanhuan; Wei, Lingmin; Li, Huogen (Frontiers in Plant Science, 2021)
Liriodendron chinense is an economically and ecologically important deciduous tree species. Although the reference genome has been revealed, alternative polyadenylation (APA), transcription factors (TFs), long non-coding RNAs (lncRNAs), and co-expression networks of tissue-specific genes remain incompletely annotated. In this study, we used the bracts, petals, sepals, stamens, pistils, leaves, and shoot apex of L. chinense as materials for hybrid sequencing. On the one hand, we improved the annotation of the genome. We detected 13,139 novel genes, 7,527 lncRNAs, 1,791 TFs, and 6,721 genes with APA sites. On the other hand, we found that tissue-specific genes play a significant role in maintaining tissue characteristics. In total, 2,040 tissue-specific genes were identified, among which 9.2% of tissue-specific genes were affected by APA, and 1,809 tissue-specific genes were represented in seven specific co-expression modules. We also found that bract-specific hub genes were associated plant defense, leaf-specific hub genes were involved in energy metabolism. Moreover, we also found that a stamen-specific hub TF Lchi25777 may be involved in the determination of stamen identity, and a shoot-apex-specific hub TF Lchi05072 may participate in maintaining meristem characteristic. Our study provides a landscape of APA, lncRNAs, TFs, and tissue-specific gene co-expression networks in L. chinense that will improve genome annotation, strengthen our understanding of transcriptome complexity, and drive further research into the regulatory mechanisms of tissue-specific genes.